TECHNICAL STACK FOR OPEN SOURCE INTELLIGENCE - Коробейнікова, Тетяна; Симак, Ігор (SWorldJournal, 2024)
Open Source Intelligence (OSINT) is an important concept, methodology, and technology that enables the collection of information from open sources. The article examines the relationship between OSINT and other types of intelligence, specifically HUMINT, w